Usaha La Sangkuru Patau Dalam Mengembangkan Agama Islam Di Kerajaan Wajo - Nasruddin Nasruddin (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2014)
La Sangkuru Patau is one of the Arung Matoa Wajo has substantial powers. His remarks could be a law and society Wajo stick to what he says. So when La Sangkuru Patau said that he had converted to Islam, the community participated Wajo also embraced Islam. Arung Matoa Wajo La Sangkuru with doing business in developing Islam in Wajo that bring Datu Sulaiman to provide Islamic religious instruction in public Wajo, then set up a sara officers' special charge of handling issues such royal Friday prayers, warnings Islamic holidays , then hold the officer cadre sara 'that will be placed outside the capital of the kingdom (Tosora), sara officers' given the facilities, such as free of taxes, as well as the parallel position to the position of indigenous stakeholders.